The Role of the Akidah Akhlak Teacher in Educating the Independent Character of Eighth Grade Students at MTS Baitul Arqom - Yuliany Yuliany; Rahmi Utami Hadiani (Penerbit Presisi Pustaka, 2026)
The teaching of Akidah Akhlak plays a strategic role in achieving the goals of Islamic Religious Education, namely forming students who are faithful, have noble morals, and an independent personality. This study aims to analyze the role of Akidah Akhlak teachers in educating the independent character of grade VIII students at MTs Baitul Arqom, as well as identifying strategies, supporting and inhibiting factors. This research uses a descriptive qualitative method with a field research approach. Data were collected through observation, interviews, and documentation. The results show that the teacher’s role is manifested through role modeling, habituation, motivation, guidance, and facilitation. The strategies applied include individual assignments, discussion methods, question and answer, discipline building, and linking material to daily life. Students’ independent character is reflected in discipline, responsibility, initiative, and independent learning. Supporting factors are a conducive school environment and the active role of teachers, while inhibiting factors are students’ low awareness and external environmental influences. Conclusion: Akidah Akhlak teachers make an important contribution to the formation of students’ independent character as part of the implementation of Islamic Religious Education.